PELESTARIAN BUDAYA BATAK MELALUI FILM NGERI-NGERI SEDAP (SEMIOTIKA CHARLES SANDERS PEIRCE) - Angel Malina Narwastu Nababan; Windhiadi Yoga Sembada (Jurnal Komunikasi dan Budaya, 2023)
The film was chosen by the writer because it highlights several scenes of Batak cultural preservation. Preservation of Batak culture is the theme of this thesis because it wants to provide new knowledge about Batak culture which is poured into a film. The representation of the preservation of Batak culture is contained in the 1 hour 53 minute horror film. The formulation of the problem raised in this research is How is the Preservation of Batak Culture in the film Horrifyingly Delicious?. The research objective that the author wants to achieve in this study is to find out the preservation of Batak culture represented in the film Ngeri-ngeri Sedap. This study uses a qualitative approach using Charles Sanders Peirce's semiotic analysis. Peirce categorizes triangle meaning which consists of three main elements, namely sign, object and interpretant. Researchers conducted an analysis of scenes or scenes related to the preservation of Batak culture. The results of this study indicate that the film Ngeri-ngeri Sedap contains the preservation of Batak culture, namely wandering, toasting Pahompu, marrying a Batak person, and the youngest child becoming the heir.